BIOADSORPSI Hg(II) OLEH PATI SAGU TAUT SILANG FOSFAT [Bioadsorption of Hg(II) by Crosslinked Sago Starch Phosphate] - Jorion Romengga; Tun Tedja Irawadi; Sr Sugiarti (Jurnal Teknologi dan Industri Pangan, 2012)
Crosslinked-sago-starch-phosphate (SgP) has been successfully synthesized from native sago starch (Sg) and Na2HPO4-NaH2PO4 in an acidic condition. The compound was designed as bioadsorbent for removing Hg(II) inside human digestion tract as shown by in vitro test. The bioadsorption followed pseudo-second order of reaction kinetic and Freundlich equation as chemisorption. As a result, 21% of Hg(II) was removed at pH of 6.80 and reached the isothermal equilibrium of the bioadsorption at pH of 5.80 and 8.60 for 29.95% and 31.39%, respectively. The result showed that SgP is more feasible than activated carbon to be used as bioadsorbent in removing Hg(II) in human digestion tract as proved by in vitro system.